Shaping Globally Minded Young Citizens Through Islamic International Education: A Case Study of Global Islamic School in Yogyakarta - Arpannudin, Iqbal; Suyato; Murdiono, Mukhamad; Charismana, Dian Satria; Hidayah, Yayuk; Yuanjaya, Pandhu; Mulyono, Budi; Alrakhman, Riza (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
This study investigates how an Islamic-based international school in Indonesia, Global Islamic School (GIS) Yogyakarta, forms globally minded young citizens through curricular and non-curricular initiatives. Amid the growing importance of global citizenship education (GCE) in the 21st century, the study explores how GIS integrates core global citizenship competencies into its educational vision, pedagogical design, and student development programs. Using a qualitative case study approach, data were collected through in-depth interviews, document analysis, and classroom observations. Findings indicate that GIS utilizes a four-pillar model within the national curriculum plus framework to cultivate a generation of globally engaged Muslim youth. Additionally, extracurricular programs such as bilingual learning days, international competitions, and educational trips abroad provide meaningful spaces for students to develop global competencies in authentic contexts. This study contributes to the discourse on faith-based approaches to global citizenship education and offers implications for schools cultivating inclusive, ethical, and globally engaged young people.